Progress in murine models of ruptured abdominal aortic aneurysm - Yin, Li; Kent, Eric William; Wang, Bowen (Frontiers in Cardiovascular Medicine, 2022)
Abdominal aortic aneurysm (AAA) is a focal dilation of the aorta that is prevalent in aged populations. The progressive and unpredictable expansion of AAA could result in aneurysmal rupture, which is associated with ~80% mortality. Due to the expanded screening efforts and progress in diagnostic tools, an ever-increasing amount of asymptomatic AAA patients are being identified yet without a cure to stop the rampant aortic expansion. A key barrier that hinders the development of effective AAA treatment is our incomplete understanding of the cellular and molecular basis of its pathogenesis and progression into rupture. Animal models provide invaluable mechanistic insights into AAA pathophysiology. However, there is no single experimental model that completely recapitulate the complex biology behind AAA, and different AAA-inducing methodologies are associated with distinct disease course and rupture rate. In this review article, we summarize the established murine models of ruptured AAA and discuss their respective strengths and utilities.